A failure analysis 115RE rail type, due to a compression load state in areas where it was placed exothermic welding copper cable for attaching electrical continuity. (September 2017) - Delgado, F.P.; Acosta, R.U.; Nieto, F.; Alcántara, S.; Sauce, V.M.
Abstract: This paper proposes the study of factors that led to the fracture of a rail type 115RE used by the "Collective Transportation System" of Mexico City. This route, is housed on concrete boxes, which are part of the railway infrastructure; which present slides due to movement due to geological faults in the area where it was built. This leads to sections of the rail being subjected to a state of compressive loads. Affecting both the cross section and the base thereof; In addition, there is an interaction that influences the area where copper solder was deposited by the exothermic method, to join electrical conductivity wire, which is housed on the base of the rail. The article is divided into three stages: The first relates to a mathematical approach related to the normal stress and the displacement of the neutral axis, in order to understand the behavior of these in the section where it was placed welding; the second, contemplates a metallographic study and characterization technique by scanning electron microscopy, in the area where the weld was deposited in order to identify possible changes in the microstructure as a result of thermal shock; also identify a growth of cracks in the boundary between the copper and steel welding; in the third, they subjected to bending metal samples obtained from the affected track section with and without welding. In order to know what changes are presented in constant mechanical and identify the genesis of the bill.